Participation of the Turkish Military in the Economy of the State: Case of Indirect Praetorionism - Špak, Valerij (Politologija, 2020)
Based on the example of the Turkish military’s involvement in the country’s economy, this article seeks to complement the concept of praetorionism and to highlight the mechanisms of indirect praetorionism. The Turkish army plays an important role in the country’s economy, while the military pension fund OYAK is considered one of the country’s business giants. It provides an opportunity to maintain disproportionate institutional autonomy and weakens civilian control mechanisms. This provides the military with additional instruments of political influence and encourages the emergence of hidden mechanisms of praetorianism. The article seeks to understand new phenomena and trends in the interaction between the society and the military, as the involvement of the Turkish army in the country’s economy changes the concept of praetorianism and provides new, indirect ways of intervening in public policy. Because of how the Turkish military controls business companies using a privileged position in the country’s economy, corruption mechanisms that influence the mechanisms of the redistribution of economic resources and the pursuit of rents have an indirect impact on the political system of the state. In this way, military entrepreneurship has transformed the conceptual structure of praetorians and complemented interventions with indirect forms of influence, such as corruption, economic dominance, and the distortion of economic reforms.